Rokitamycin Induces a Mitochondrial Defect and Caspase-Dependent Apoptosis in Human T-Cell Leukemia Jurkat Cells - Masayuki Fukui; Yukitoshi Nagahara; Yoshiaki Nishio; Tsutomu Honjoh; Takahisa Shinomiya (Elsevier, 2009)
Abstract.: Macrolides are a well-known family of oral antibiotics whose antibacterial spectrum of activity covers most relevant bacterial species responsible for respiratory infectious disease. In recent years, it has been reported that macrolides have not only bactericidal activity but also direct immunomodulating activity in mammals. In this study, we observed new physiological activity of macrolides and examined whether various macrolides induce apoptosis in human leukemia cell lines. We investigated the effects of 13 different macrolides on the viability of Jurkat and HL-60 cells. Among all the macrolides used in this study, rokitamycin, a semisynthetic macrolide with a 16-member ring, effectively induced cell death. Rokitamycin induced DNA fragmentation and caspase activation, resembling the progression of apoptosis. Moreover, rokitamycin reduced the mitochondrial transmembrane potential and released cytochrome c from mitochondria to the cytosol, suggesting that mitochondrial perturbation is involved in rokitamycin-induced apoptosis. These results suggest that rokitamycin possesses not only bactericidal activity but also pro-apoptotic activity in human leukemia cells. Keywords:: macrolide, rokitamycin, apoptosis, mitochondria, caspase